2010
DOI: 10.1007/s10494-010-9305-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lewis Number on Scalar Variance Transport in Premixed Flames

Abstract: The influences of differential diffusion rates of heat and mass on the transport of the variances of Favre fluctuations of reaction progress variable and non-dimensional temperature have been studied using three-dimensional simplified chemistry based Direct Numerical Simulation (DNS) data of statistically planar turbulent premixed flames with global Lewis number ranging from Le = 0.34 to 1.2. The Lewis number effects on the statistical behaviours of the various terms of the transport equations of variances of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 59 publications
(164 reference statements)
5
69
0
Order By: Relevance
“…Re t = ρ 0 u l/μ 0 , where ρ 0 and μ 0 are the unburned gas density and viscosity respectively) were not addressed. Chakraborty and Swaminathan [10] extended the RANS-K model [22] for non-unity Lewis number flames and obtained good agreement with DNS data even for small values of Damköhler number (i.e. Da < 1).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Re t = ρ 0 u l/μ 0 , where ρ 0 and μ 0 are the unburned gas density and viscosity respectively) were not addressed. Chakraborty and Swaminathan [10] extended the RANS-K model [22] for non-unity Lewis number flames and obtained good agreement with DNS data even for small values of Damköhler number (i.e. Da < 1).…”
Section: Introductionmentioning
confidence: 94%
“…The relation <ẇ >= 2 < ρ>Ň c /(2c m − 1) (where < Q > andQ =< ρQ > / < ρ > are the Reynolds averaged and Favre averaged values of a general quantity Q respectively) can be derived based on the balance of the reaction rate and scalar dissipation rate contributions to the scalar variance transport in the context of RANS for Da >>1.0 flames where the pdf of c shows high probability of finding both unburned and completely burned gases, and small probability of finding burning mixtures [5]. Chakraborty and Cant [9] demonstrated based on scaling arguments [10] that <ẇ >= 2 < ρN c > /(2c m − 1) remains valid even for Da < 1 flames as long as the flamelet assumption holds. It has been demonstrated earlier [6][7][8] thatw = 2ρÑ c /(2c m −1) can be used for filtered reaction ratew closure for >> δ th .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The direct relationship between averaged reaction rate and scalar dissipation rate in high Damköhler number flames was shown by Bray (1979Bray ( , 1980 for RANS methodology, which was also shown to hold for low Damköhler number combustion (Chakraborty and Cant, 2011;Chakraborty and Swaminathan, 2011). Dunstan et al (2013) demonstrated its applicability for LES, which is supported by subsequent analyses using DNS and LES (Butz et al, 2015;Ma et al, 2014).…”
Section: Algebraic Closure For Filtered Reaction Ratementioning
confidence: 76%